Religion and the workplace: pluralism, spirituality, leadership - Hicks, Douglas A. (Cambridge University Press, 2003)
How can company leaders and employees negotiate their different religious and spiritual commitments in the workplace? At a time of international debate over religious conflict and tolerance, workforces in various parts of the world are more diverse than ever before. Religion and spirituality are, for many employees, central to their identities. From the perspective of the employer, however, they can be distracting or divisive influences. This book analyzes the current interest in religion and spirituality in US companies. It offers conceptual distinctions and comparative examples (from the pluralistic contexts of India and Singapore) to trace the myriad ways that religion is present at work. It offers a model of respectful pluralism, asserting that the task of effective and ethical leadership in organizations is not to promote a single spiritual or religious framework but to create an environment in which managers and employees can respectfully express their own beliefs and practices.